The Spiritual Care Competency of the Nurses of the Teaching Hospitals Affiliated to Alborz University of Medical Sciences, Iran - M Mardani Hamooleh; N Seyedfatemi; A Eslami; SH Haghani (نشریه پرستاری ایران, 2020)
Background & Aims: Spiritual care is to help the individuals with challenged beliefs, values, purpose, and meaning of life, which occurs when patients are faced with severe diseases. Under such circumstances, nursing care is focused on the provision of spiritual care. Accordingly, spiritual care has been emphasized and acknowledged in the nursing profession, so that the provision such care could reduce physical pain, induce mental relief, reduce depression and anxiety, accelerate recovery, increase hope, and enhance the communication of the patient and nurse. From a deeper perspective, the provision of spiritual care by nurses to patients promotes the personal growth of the nurses. Meanwhile, attention to the spiritual care competency skills of nurses could be valuable as it seems that nurses are able to provide better care to patients by using these skills in the complex clinical setting. In fact, the competence in spiritual care is a concept involved in creating standard nursing care for patients, which encompasses a set of skills used in the nursing profession with a special status in the nursing process, as well as components such as the communication between the nurse and patient, availability to the patient, active listening, showing empathy and sympathy to value the life of the patients and give hope to the patient, facilitating spiritual skills for the patients with special beliefs, helping patients to create a calm atmosphere, and referring patients to specialists in spirituality. Although some studies have been focused on the phenomenon under study in some regions of the country, the emergence of this phenomenon in the field of nursing ethics requires these studies to highlight the need for further research regarding this concept in order to bridge the gap in the nursing knowledge in the other regions of the country, so that the obtained results could be compared. The present study aimed to evaluate the spiritual care competency of the nurses employed at the teaching hospitals affiliated to Alborz University of Medical Sciences, Iran. Materials & Methods: This descriptive, cross-sectional study was conducted on 200 nurses employed at the teaching hospitals affiliated to Alborz University of Medical Sciences (Kamali, Shariati, Imam Hossein, Madani, and Rajaei hospitals) in 2019 during four months. The subjects were selected via convenience sampling. Data were collected using demographic questionnaires containing data on the age, gender, marital status, education level, work experience, average working hours per month, ward of employment, employment status, work shifts, and organizational position. In addition, the valid and reliable tool of spiritual care competency was used for data collection. To assess the content validity, the tool was provided to five faculty members of the School of Nursing and Midwifery of Iran University of Medical Sciences, and their corrective comments were applied to the tools. The reliability was also evaluated using the retest method. For this purpose, the instruments were provided to 15 individuals, who were identical to the research samples but not included in the sample population, at two-week intervals twice, and the Pearsonchr('39')s correlation-coefficient obtained from the two tests was calculated to be 0.86. Data analysis was performed in SPSS version 16 using descriptive statistics (frequency, percentage, mean, and standard deviation) and inferential statistics (independent t-test and analysis of variance). To comply with ethical considerations, the researcher obtained the ethics code from Iran University of Medical Sciences, followed by the letter of recommendation, and made the required arrangements with the management of the selected hospitals. In addition, informed consent was obtained from the participants for enrollment, and they were justified about the research procedures, while also ensured that participation in the study was completely voluntary. In addition, the participants were assured of the confidentiality and anonymity of the data. Results: The majority of the nurses were aged 20-30 years (57%), female (81%), and married (70%). In addition, the majority of the participants were nurse (96%), had a BSc (94.5%), and worked in rotational shifts (89%). The total mean score of the spiritual care competency of the nurses was 54.21±14.69; considering the median of the instrument (=81), this finding indicated that the total score of spiritual care competency of the nurses was lower than the median. Among the demographic characteristics of the nurses, spiritual care competency was significantly correlated with the organizational position (P=0.005) and nursing work experience (P=0.003), and the spiritual care competency of the nurses was significantly higher compared to the head nurses. In addition, the spiritual care competency of the nurses with the work experience of 1-5 years was higher compared to the others. Conclusion: According to the results, the spiritual care competency of the nurses did not have a favorable status. Therefore, proper opportunities should be provided to promote their knowledge in this regard. In fact, the results of this study could lay the groundwork for further investigations and interventional studies in this regard. In other words, the recognition of the spiritual care competency of nurses in general and in terms of various dimensions in particular is an important step toward its promotion, resulting in the expansion of the views of nurses toward this concept. It seems that through spiritual care competency, nurses will be able to provide more comprehensive nursing care to patients. As such, nursing managers must take the necessary measures to enhance the spiritual care competency of nurses, among the most important of which are the implementation of educational workshops based on the concepts of spirituality and spiritual care for nurses, so that they could achieve spiritual care competency more efficiently in their profession. One of the limitations of this study was the emotional state of the sample while completing the research instruments, which could not be controlled by the researcher. Furthermore, the subjects were selected via convenience sampling, and the non-probability of the sampling method may restrict the generalizability of the findings.